Patient safety educational interventions: A systematic review with recommendations for nurse educators - Seung Eun Lee; Brenna L. Morse; Na Won Kim (Wiley, 2022)
Abstract Aim This study identified and evaluated tested patient safety educational interventions. This study also described the content, curricular structures and teaching strategies of the educational interventions and determined the methods used for evaluating patient safety learning outcomes. Design The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines directed this review. Methods Searches for articles describing and evaluating patient safety educational interventions were conducted using four scholarly databases. Study quality was assessed using the McMaster Critical Review Form. Results Seven studies met the inclusion criteria. Educational interventions were either presented as stand‐alone courses or as lessons embedded in an existing course. All studies employed a mixture of various teaching modalities and several evaluation methods and outcomes. Mixed results were observed in terms of the effects of educational interventions. Future researchers should continue to develop patient safety curricula and examine their effect on student competencies with stronger methodological rigour.